What’s It Like Being Us: Stories of Young New Zealanders Who Experience Difficulty Learning - Marshall, Sheryn A (Auckland University of Technology, 2005)
This narrative inquiry examines the stories told by eight young New Zealanders who have experienced specific difficulties with learning. At the time of being interviewed, they were aged from 9-14 years and participating in regular school classes. For the purposes of the study, being a student was identified as a key occupational role and failing to achieve tasks associated with this role was viewed as failure to achieve role competency. The issue of learning difficulties has been extensively researched but rarely from the perspective of young people. A primary goal of the study was to obtain young people's perceptions of the experience of learning difficulties. This is consistent with international moves to obtain the views of young people through research. Narrative interviewing procedures were used and participants were invited to talk about the things they enjoyed doing and felt they are good at doing, as well as the things they had trouble doing. They proved to be capable informants and provided a rich range of narrative data. Interviews were audio taped, transcribed and interview transcripts were synthesised into a story format. Each participant had the opportunity to check their story and give their final consent to its use as data in this thesis. As part of the analytical process, core narratives were constructed to capture the essence of each participant's story, their unique narrative voice, relationship with others and fundamental message. These narratives are presented in full, introducing participants as characters in their own story and revealing the nature of the stories told. In addition, thematic narratives drawn from the stories have been collated into three key categories, which relate to self and learning efforts, relationship with the social world and being occupational. The narrative analysis found that learning difficulties occurred as a negative interruption in the progressive course of participants' story, with the potential to compromise their sense of identity and well-being. However, the study also found that when participants chose to characterise themselves in relation to occupations or roles in which they felt most successful, they were able to express a more positive and holistic identity than that of being "learning disabled". Furthermore, in the context of an occupational narrative that included their talents and abilities, learning difficulties were not necessarily the determining factor in how life was for them or where their lives might go. The implication of the study's findings relate to the importance for young people of not only experiencing competency in significant occupations and roles, but also being seen to be competent. This underpins a positive sense of identity and well-being, which is likely to link to their future. They need to understand for themselves and for those around them to understand, that it is possible to be intelligent yet have trouble with basic numeracy and literacy skills. Empathetic adults have a vital role to play in providing the information, opportunities and supportive context in which young people develop an understanding of their occupational competencies and become competent human beings. There is a place for further narrative research with young New Zealanders; there are many stories from other perspectives yet to be told. Ongoing research conducted through an occupational lens is needed to understand the way in which young people with learning difficulties develop, or fail to develop, an understanding of themselves as competent occupational beings and how this supports or constrains their transition through adolescence into adulthood. Note: An addendum statement was added to this record on July 31, 2026.
Keywords: Children's experiences of learning difficulties; Specific learning difficulties; Occupational identity; Narrative research; Education